Feasibility Study of Investment in Clean Water System of Tirta Tuah Benua Drinking Water Company, East Kutai, Sangatta City - Suparjan, Suparjan; Oetomo, Wateno; Marleno, Risma (LPPM of NAROTAMA UNIVERSITY, 2025)
Clean water is water that is used for daily needs and becomes drinking water after being boiled first. The distribution system is a system that is directly related to consumers, which has the main function of distributing water that has met the requirements to all service areas. In addition to the problem of the clean water supply system, the problem of the capacity of the clean water treatment system (IPA) is also an obstacle with the continued growth of the population in the future. The need for clean water that meets health standards continues to increase every year, which is also experienced by Sangatta City which is in line with the increase in population and public awareness of health. Based on the background of this problem, the title of this study is Feasibility Analysis of Investment in the Clean Water System of Perumda Air Minum Tirta Tuah Benua Kutai Timur Sangatta City. The solution method in this calculation for the Feasibility Investment Analysis uses the Net Present Value (NPV) method, the Break Event Point (BEP) method. From the results of the analysis, it was obtained that the NPV value was Rp 29,586,543,082 (NPV> 0). So the investment in developing the production capacity and clean water network of Perumda Air Minum Tirta Tuah Benua, Kaliorang District, is feasible to continue. A positive NPV value or greater than (> 0) indicates that the income is greater than the invested value. The return value is obtained in the 9th year, marked by the accumulation of minus profits becoming positive after the 9th year. This explains that the investment in replacing the clean water distribution network of Perumda Air Minum Tirta Tuah Benua, Kaliorang District is feasible to run, because there is a return on investment as evidenced by the BEP value for 9 years.